Avaliação da presença de contaminantes fúngicos e bacterianos na água e no ar de biotério para roedores utilizado para pesquisas científicas - Silva, Luiz Márcio da (2022)
Microbial contamination in animal facilities is hazardous for both humans and animals. Hence, sanitary standards should always be maintained to prevent microbial contamination in these facilities. This study aimed to evaluate the level of air and water contamination and identify the isolated microbial of rodent facility located at the Federal University of Uberlandia, Minas Gerais, Brazil. Colony forming units (CFU) per milliliter was used for quantitatively monitoring water, while CFU per cubic meter was used for air. Microbial identification of isolated colonies was performed for qualitative monitoring. The total mean number of microorganism in water ranged from 0.015 ± 0.02 to 0.999 ± 0.91 CFU/mL. The number of microorganism in air ranged from 9.1 ± 4.6 to 351.56 ± 158.2 CFU/m³. Forty-one microorganisms identified in the samples of the rodent facility were potentially pathogenic and/or opportunistic for both animals and humans. Concluding that both water and air samples showed contamination of potentially pathogenic and opportunistic microorganisms that can harm both rodents and humans. On the basis of our observations, specific sanitary standards suitable for these facilities should be developed for controlling microbial contamination, which will prevent zoonosis and ensure reliability in scientific results of animal experiments.